VD_FINDINFO Pron / 2013 / 176 vom 2. Juli 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, MESURE PROVISIONNELLE, DIVORCE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)